Pengaruh Video Influencer Di Sosial Media Terhadap Keputusan Pembelian Produk Perawatan Tubuh Pada Mahasiswa Politeknik Bisnis Indonesia - Hengki Mangiring Parulian Simarmata; Poltak Pardamean Simarmata; Doris Yolanda Saragih; Nancy Florida Siagian (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The development of social media platforms encourages companies to develop marketing strategies on various social media platforms. One of the marketing strategies is done by using influencers. This study aims to determine the effect of video influencers on purchasing body care products for students of the Pematang Siantar Indonesian Business Polytechnic. This type of research is quantitative research with a sample of 173 respondents. The sample is all active students of the Indonesian Business Polytechnic who use body care products. The data is collected and then tested on the validity, reliability, classic assumption, and normality tests. The analysis technique uses simple linear analysis with the help of SPSS. The results of the study show that there is a significant positive influence from video influencers on purchasing decisions for body care products. The effect of Video Influencers is 41.5%, while the remaining 58.5% is influenced by other variables not examined in this study, such as price variables, price discounts, influencers used, and others.